Factors Influencing Exclusive Breastfeeding Practices In Rural Indonesia: Evidence From Lampung Province - Ningrum, Allania Hanung Putri Sekar; Kartikasari, M. Nur Dewi; Sulistiani, Ardiani (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2025)
Background: Breast milk is an ideal food for babies. Breast milk has benefits not only for the baby but also for the mother and the environment. However, the exclusive breastfeeding rate in Indonesia and the world is still low. Purpose: This study aims to find the factors that cause low exclusive breastfeeding in rural areas in Indonesia. Methods: this study is quantitative research with a cross-sectional approach. The sample involved in this study was 164 mothers who had children aged 0-6 months in 6 villages. The analysis used in this study is bivariate and multivariate. Results: There was no statistically significant association between mothers' work and exclusive breastfeeding in rural areas. The mother's age and parity are also unrelated to exclusive breastfeeding. Income, education, infant age, first breastfeeding opportunities, delivery methods, and delivery aides contributed 20.1% to exclusive breastfeeding of infants aged 0-6 months in rural areas. Conclusion: This study is useful to find out the factors related to exclusive breastfeeding in rural areas in Lampung.